Factors influencing development of trans urethral resection of prostate (TURP) syndrome in benign prostatic hyperplasia patients with various co morbid medical illness: a prospective study - K. J., Narayanan; V. P., Kannan (International Journal of Research in Medical Sciences, 2017)
Background: The aim of this prospective study is to analyse the factors influencing development of trans urethral resection of prostate (TURP) syndrome in benign Prostatic hyperplasia patients with various co morbid medical illness in Thanjavur Medical College Hospital, from February 2015 to January 2017. Methods: This prospective study was done among 38 benign hyperplasia prostate patients with various co morbid medical illness underwent TURP. Pre-operative and post-operative serum sodium levels correlated with signs and symptoms developed in various prostate gland sizes, resection times and volume of irrigation fluids. Results: Sodium level has gone down to 14 meq/L, gone up to 2 meq/L post-operatively. Major fluctuations in serum sodium was seen in prostate size more than 50 grams, resection time more than 40 mints, irrigant volume more than 24 litres. Mean sodium decrease was increased when gland size was increased, resection time was increased, irrigant volume was increased. Conclusions: In renal insufficiency patients, it is safe to complete the procedure within 40 minutes and restrict irrigant volume 15 litres, in coronary artery disease patients it is safe to restrict irrigant fluid volume less than 20 litres. In Diabetes Mellitus patients, it is safe to restrict irrigant fluid volume less than 24 litres. In hypertensive patients, it is safe to restrict the resection time less than 45 minutes. In patients with Diabetes and hypertension, it is safe to restrict the resection time less than 40 minutes and irrigant fluid less than 20 litres.